Impaired perception of temporal contiguity between action and effect is associated with disorders of agency in schizophrenia - Roth, Manuel J.; Lindner, Axel; Hesse, Klaus; Wildgruber, Dirk; Wong, Hong Yu; Buehner, Marc J. (Proceedings of the National Academy of Sciences - PNAS, 2023)
Delusions of control in schizophrenia are characterized by the striking feeling that one’s actions are controlled by external forces. We here tested qualitative predictions inspired by Bayesian causal inference models, which suggest that such misattributions of agency should lead to decreased intentional binding. Intentional binding refers to the phenomenon that subjects perceive a compression of time between their intentional actions and consequent sensory events. We demonstrate that patients with delusions of control perceived less self-agency in our intentional binding task. This effect was accompanied by significant reductions of intentional binding as compared to healthy controls and patients without delusions. Furthermore, the strength of delusions of control tightly correlated with decreases in intentional binding. Our study validated a critical prediction of Bayesian accounts of intentional binding, namely that a pathological reduction of the prior likelihood of a causal relation between one’s actions and consequent sensory events—here captured by delusions of control—should lead to lesser intentional binding. Moreover, our study highlights the import of an intact perception of temporal contiguity between actions and their effects for the sense of agency.